HUBUNGAN PEMBELAJARAN BERBASIS PROYEK DALAM MEWUJUDKAN PEMBELAJARAN ABAD 21 PADA SISWA KELAS IV SDN TAMANSARI II - Mustika Kirana Putri; Didit Yulian Kasdriyanto; Ribut Prastiwi Sriwijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the relationship between project-based learning in realizing 21st century learning in grade IV students of SDN Tamansari II. In this study, the research design used a quantitative approach with a pre-experimental one group pretest posttest design. The population in this study were all grade IV students of SDN Tamansari II in the 2024/2025 academic year with a sample size of 20 students. Data collection in this study used a pretest and posttest which functioned to determine student learning outcomes before and after being treated. The study was conducted by testing the hypothesis using the